Directed trees in multicast routing - Nicolau, Maria João (2003)
Traditional multicast routing protocols use RPF (Reverse Path Forwarding) concept to build multicast trees. This concept is based upon the idea that an actual delivery path to a node is the reverse of the path from this node to the source. This concept fits well in symmetric environments, but in a routing environment where Quality of Service is considered the guarantee that a symmetrical path will exist between two network addresses is broken. Available network resources impose specific Quality of Service asymmetries, therefore reverse path routing may not be used. In this paper a new multicast routing strategy is proposed, enabling directed trees establishment, instead of reverse path ones. This new strategy, DTMP- Directed Trees Multicast Routing, is then implemented and simulated using Network Simulator. Simulation results, driven from several scenarios are presented, analyzed and compared with PIM-SM.